Development and Investigation of a Separation Process Within Cross-Flow with Superimposed Electric Field - Simon Paas; Kai Nikolaus; Sergiy Antonyuk (Powders)
The increasing demand for highly specific particulate products in industrial processes is a driving factor in the development of novel particle separation processes. In this work, a multidimensional separation process for wet simultaneous separation by hydrodynamic diameter and electrophoretic mobility was developed. The hydrodynamic effects and electrophoretic influences within this process were experimentally investigated on different scales with three setups for batch and continuous operation. Flow rates were varied from a few mL∙min−1 to several 100 L∙h−1, and electric field strengths of up to 300 V∙cm−1 were employed to analyze different spherical particles in the range of 1 to 100 µm. The investigations demonstrated the limitation of the separation process due to some of the resulting effects, such as electrolysis. A scale-up approach for hydrodynamic separation was developed based on CFD simulation, which can predict the operating range of the process with the high efficiency.